Tafila Region Wind Power Projects : Cumulative Effects Assessment - International Finance Corporation (Washington, D.C., 2017)
The Tafila Region Wind Power Project Cumulative Effects Assessment (CEA) is the first of its kind in the Eastern Europe, Middle East, and North Africa region. It aims to promote more sustainable wind energy investments in Jordan while assessing and managing potential adverse environmental and social effects of renewables. The overall management and technical direction of the CEA was undertaken by IFC, supported by a team of multidisciplinary international and Jordanian experts and advisors.